Speciation with gene flow between two Neotropical sympatric species (Pitcairnia spp.: Bromeliaceae) - Marília Manuppella Tavares; Milene Ferro; Bárbara Simões Santos Leal; Clarisse Palma‐Silva (Ecology and Evolution, 2022)
Abstract The study of mechanisms that generate new species is considered fundamental for broad areas of ecology and evolution. Speciation is a continuous process in which reproductive isolation is established, and it is of fundamental importance to understand the origins of the adaptations that contribute to this process. Hybrid zones are considered natural laboratories for the study of speciation and represent ideal systems for such studies. Here, we investigated genomic differentiation between hybridizing Neotropical species Pitcairnia staminea (G. Lodd.) and P. albiflos (Herb.). Using thousands of SNPs genotyped through RAD‐seq, we estimate effective population sizes, interspecific gene flow, as well as time of divergence between these two sister species and identify candidate genomic regions for positive selection that may be related to reproductive isolation. We selected different scenarios of speciation and tested them by using approximate Bayesian computation (ABC); we found evidence of divergence with gradual reduction in gene flow between these species over time, compatible with the hypothesis of speciation with gene flow between these Pitcairnia species. The parameter estimates obtained through ABC suggested that the effective population size of P. albiflos was around three times larger than that of P. staminea. Our divergence date estimates showed that these two species diverged during the Pliocene (4.7 Mya; CI = 1.3–8.5 Mya), which has likely allowed this species to accumulate genome‐wide differences. We also detected a total of 17 of 4165 loci which showed signatures of selection with high genetic differentiation (FST > 0.85), 12 of these loci were annotated in de novo assembled transcriptomes of both species, and 4 candidate genes were identified to be putatively involved in reproductive isolation. These four candidate genes were previously associated with the function of pollen development, pollen tube germination and orientation, abiotic stress, and flower scent in plants, suggesting an interplay between pre‐ and postpollination barriers in the evolution of reproductive isolation between such species.